Effects of complex decongestive physical therapy on upper limb circumference and sensory function in post-mastectomy lymph oedema, A quasi-experimental study - Nawaz, Momena; Bashir, Muhammad Salman; Noor, Rabiya; Ikram, Mehwish (Journal of the Pakistan Medical Association, 2024)
The quasi-experimental study was conducted at the Allied Hospital, Faisalabad to investigate the effect of complex decongestive physical therapy on sensory testing in post-mastectomy-related lymphoedema patients. The sample comprised 18 participants enrolled using convenience sampling technique. All the participants received complex decongestive physical therapy during 5 sessions per week for 3 weeks. The intervention comprised manual lymphatic drainage, multi-layered compression bandages, skin care and patient-oriented exercises for breast cancer-related lymphoedema. Upper limb circumference of the subjects was measured, while two-point discrimination test, pressure pain threshold test and tactile localisation test were also conducted. Complex decongestive physical therapy showed a significant difference in pre- and post-intervention values (p<0.05). Complex decongestive physical therapy was found to be effective in improving sensory perceptions, like discrimination, tactile and pain pressure threshold, as well as oedema. Key Words: Compression bandages, Mastectomy, Quality of life, Range of motion, Breast cancer lymphoedema.